Driving SME Performance: The Impact of Competence and Entrepreneurial Orientation - Sapta, I Ketut Setia; Utami, Ni Made Satya; Rustiarini, Ni Wayan; Abantao, Banilline Jone V. (International Review of Management and Marketing, 2025)
The purpose of this study is to determine and analyse the influence of competence and entrepreneurial orientation on the performance of SMEs. This study also examined the influence of Catur Purusa Artha in moderating the impact of entrepreneurial competence on the performance of SMEs. The sample in this study was the owner or manager of small and Medium Enterprises (SMEs) in Bali Province in 2022, which amounted to 350 units of SMEs. The data analysis technique is done by the SEM-PLS method. The analysis showed that entrepreneurial competence has a significant positive effect on the performance of SMEs, but entrepreneurial orientation does not affect their performance. Meanwhile, the cultural values of Catur Purusa Artha weakened the relationship between entrepreneurial competence and SME Performance. Other results showed that Catur Purusa Artha variables strengthened the relationship between entrepreneurship orientation and SME performance.